Risk factors of acute malnutrition in children from six to twenty four months treated in Hospitals in three districts of Huánuco - 2005 - Fernández-Ginés, Tania (2019)
To identify risk factors associated to acute malnutrition in children from six to twenty-four months, treated in hospitals in Huánuco district – 2005. A study of cases and controls were designed, and 181 cases with acute malnutrition with the same number of eutrophic controls were selected. The interview and survey were applied to mothers or relatives who take care of children. The bivariate analysis to estimate possibility ratios and confidence intervals (CI 95%) was performed; statistical differences were analyzed using the X2 Test of Pearson. Significant variables were: incomplete immunization, presence of acute respiratory infections, diarrheal diseases, literacy rate of mother, integral care of the child, rate of absence to control growth and development, practice of washing hands of child, breastfeeding, age of onset of complementary feeding, frequency of servings per day, lack of drinking water supply, inadequate conservation of toilets or latrines, low family income, reduced spending in food, insufficient guidance and counseling on nutrition and child care, inappropriate treatment of staff health and delay in health care. Concluding that biological factors, maternal factors, dietary practices, environmental factors, socioeconomic factors, and factors of health service supply are decisive in cases for acute malnutrition.